2017
DOI: 10.3390/ijms18102051
|View full text |Cite
|
Sign up to set email alerts
|

Neuron–Glia Crosstalk and Neuropathic Pain: Involvement in the Modulation of Motor Activity in the Orofacial Region

Abstract: Neuropathic orofacial pain (NOP) is a debilitating condition. Although the pathophysiology remains unclear, accumulating evidence suggests the involvement of multiple mechanisms in the development of neuropathic pain. Recently, glial cells have been shown to play a key pathogenetic role. Nerve injury leads to an immune response near the site of injury. Satellite glial cells are activated in the peripheral ganglia. Various neural and immune mediators, released at the central terminals of primary afferents, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 129 publications
(286 reference statements)
3
35
0
6
Order By: Relevance
“…However, the effects of MAGL inhibitors on animal models of orofacial neuropathic pain have not been assessed. Injury to the trigeminal nerve in the orofacial area induced neuropathic pain in animal models (26)(27)(28)(29)(30). This type of nerve injury causes sensitization of the peripheral and central nervous systems (e.g., allodynia and hyperalgesia), which are typical characteristics of neuropathic pain (2,28,29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of MAGL inhibitors on animal models of orofacial neuropathic pain have not been assessed. Injury to the trigeminal nerve in the orofacial area induced neuropathic pain in animal models (26)(27)(28)(29)(30). This type of nerve injury causes sensitization of the peripheral and central nervous systems (e.g., allodynia and hyperalgesia), which are typical characteristics of neuropathic pain (2,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Injury to the trigeminal nerve in the orofacial area induced neuropathic pain in animal models (26)(27)(28)(29)(30). This type of nerve injury causes sensitization of the peripheral and central nervous systems (e.g., allodynia and hyperalgesia), which are typical characteristics of neuropathic pain (2,28,29). Furthermore, use of the synthetic cannabinoid WIN 55,212-2 was recently reported to attenuate allodynia and hyperalgesia caused by chronic constriction injury of the infraorbital nerve (ION) (31).…”
Section: Introductionmentioning
confidence: 99%
“…CB2 receptors are also present in glial cells (e.g., microglia), which were observed to be upregulated following inflammation or nerve injury [109][110][111][112]. Microglia are important mediators for neuropathic pain development [113][114][115]. Various studies have reported that reactive microglia interact with neurons and contribute to the development of neuropathic pain [113][114][115].…”
Section: Modulation Of Cb2 Receptor Expression Under Neuropathic Painmentioning
confidence: 99%
“…Microglia are important mediators for neuropathic pain development [113][114][115]. Various studies have reported that reactive microglia interact with neurons and contribute to the development of neuropathic pain [113][114][115]. In different models of neuropathic pain such as peripheral nerve injury, chemotherapy-induced neuropathic pain and chronic post-ischemia pain, CB2 receptor expression is increased in microglia [110,116,117].…”
Section: Modulation Of Cb2 Receptor Expression Under Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation